2019
DOI: 10.1111/jnp.12192
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related cognitive decline in myotonic dystrophy type 1: An 11‐year longitudinal follow‐up study

Abstract: Background Myotonic dystrophy type 1 (DM1) is an inherited multi‐systemic disease involving the central nervous system (CNS) and is consequently characterized by a range of cognitive impairments. However, whether this cognitive profile progresses over time is still a matter of debate. The aim of this study was to longitudinally assess a DM1 sample, in order to compare, for the first time, this progression with that of a control group. Clinical and socio‐demographic predictive factors potentially implicated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
1
19
1
1
Order By: Relevance
“…1 Furthermore, from a neuropsychological perspective, recent findings suggest that cognitive functions suffer a decline in several areas, beyond that expected in normal aging. [2][3][4][5][6] Although neuroimaging data are thought to support the previously suggested hypothesis of neurodegenerative processes in DM1, to the best of our knowledge, there have been only two previous attempts to longitudinally study a hypothesized progressive impairment in brain structures. While Gliem et al 7 did not find a greater volume loss over time in DM1 for either gray or white matter tissue, Conforti et al found a progression in white matter lesions along with greater brain atrophy assessed by the ventricular/brain ratio.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…1 Furthermore, from a neuropsychological perspective, recent findings suggest that cognitive functions suffer a decline in several areas, beyond that expected in normal aging. [2][3][4][5][6] Although neuroimaging data are thought to support the previously suggested hypothesis of neurodegenerative processes in DM1, to the best of our knowledge, there have been only two previous attempts to longitudinally study a hypothesized progressive impairment in brain structures. While Gliem et al 7 did not find a greater volume loss over time in DM1 for either gray or white matter tissue, Conforti et al found a progression in white matter lesions along with greater brain atrophy assessed by the ventricular/brain ratio.…”
Section: Introductionmentioning
confidence: 83%
“…CNS studies with a focus on brain pathology have defined DM1 as a combination of tauopathy, spliceopathy, and RNAopathy, all of which contribute to neurodegeneration 1 . Furthermore, from a neuropsychological perspective, recent findings suggest that cognitive functions suffer a decline in several areas, beyond that expected in normal aging 2–6 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, congenital and childhood-onset DM1 patients suffer mental retardation, whereas patients with the adult-onset forms may show varying degrees of cognitive dysfunction, where a positive correlation between triplet expansion length and patients’ age is observed. Nowadays, there are data supporting an age-dependent progressive cognitive decline in DM1 patients [ 35 ], that correlates with brain atrophy [ 36 ].…”
Section: Myotonic Dystrophy and Aging: Link At Clinical Levelmentioning
confidence: 99%
“…The 12‐year study of 16 DM1 patients did not show significant longitudinal changes 35 . In a much larger longitudinal study comparing DM1 participants and controls, significant changes occurred after 11 years, but only on measures that assessed visual‐spatial/construction abilities and visual memory, 6 whereas performance on measures of attention, reaction time, verbal abilities, verbal memory, and executive functioning did not change significantly. In fact, the only significant change over time in our study was apparent improvement of executive function from baseline to 3 months, as determined by the GMLT, which suggested a learning or practice effect.…”
Section: Discussionmentioning
confidence: 84%